2012
DOI: 10.1177/1470320312460899
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain-attenuating potential of aliskiren in chronic constriction injury model in rats

Abstract: The present study was designed to investigate the potential of aliskiren, a direct renin inhibitor, in chronic constriction injury (CCI)-induced neuropathic pain in rats. Neuropathic pain was induced by placing four loose ligatures around the sciatic nerve. Acetone drop, von Frey hair, pin-prick and hot plate tests were performed to assess cold allodynia, mechanical allodynia, mechanical and heat hyperalgesia, respectively. The levels of Tumor necrosis factor-alpha (TNFa) were measured in the sciatic nerve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
1
18
0
2
Order By: Relevance
“…11,14 RAAS mediated release of excess angiotensin II is a major culprit in the development of neuropathic pain sensitivity via angiotensin I and angiotensin II receptors. 17,20 Recent reports show that angiotensin I receptor blockers, i.e. telmisartan, produce an ameliorative effect against CCI-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,14 RAAS mediated release of excess angiotensin II is a major culprit in the development of neuropathic pain sensitivity via angiotensin I and angiotensin II receptors. 17,20 Recent reports show that angiotensin I receptor blockers, i.e. telmisartan, produce an ameliorative effect against CCI-induced neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Various pathological mechanisms and targets are explored in the development of CRPS in humans as well as experimental animals. 9 A recent study reported that RAAS plays a critical role in the management of neuropathic pain disorders, 17,19,21 as RAAS activation is due to the peripheral nerve injury associated with sympathetic outflow in secondary and tertiary neurons at spinal cord and dorsal root ganglion. 11,14 RAAS mediated release of excess angiotensin II is a major culprit in the development of neuropathic pain sensitivity via angiotensin I and angiotensin II receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of different doses of aliskerin (a direct renin inhibitor), telmisartan (AT 1 receptor antagonist with highest affinity) and spironolactone (aldosterone receptor antagonist) for 14 days attenuated neuropathic pain in terms of decrease in paw cold allodynia, mechanical allodynia and heat hyperalgesia in CCI-induced neuropathic pain in rats. 26,27,34 A study from another laboratory has also demonstrated the dose-dependent anti-nociceptive actions of systemically administered aliskerin in the writhing, formalin hindpaw, capsaicin-induced pain, post-operative pain, CCI-induced neuropathic pain and orofacial pain tests in mice. 35 A study from our laboratory has also reported the anti-hyperalgesic effect of spironolactone in diabetic neuropathic pain.…”
Section: Preclinical Studiesmentioning
confidence: 99%